2010
DOI: 10.1109/tit.2009.2034781
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Absorbing Sets and Fully Absorbing Sets of Array-Based LDPC Codes

Abstract: The class of low-density parity-check (LDPC) codes is attractive, since such codes can be decoded using practical message-passing algorithms, and their performance is known to approach the Shannon limits for suitably large block lengths. For the intermediate block lengths relevant in applications, however, many LDPC codes exhibit a so-called "error floor," corresponding to a significant flattening in the curve that relates signal-to-noise ratio (SNR) to the bit-error rate (BER) level. Previous work has linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
195
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(201 citation statements)
references
References 29 publications
6
195
0
Order By: Relevance
“…We first show in Lemma 1 that (4, 8) absorbing sets indeed exist for this r = 5 array-based code family. This theoretical result is also consistent with previous experimental results of a sum-product decoding algorithm built in software and on a hardware emulator [30] for which it was shown that decoding errors due to (4,8) absorbing sets dominate the low BER region. This error floor region is determined by noncodewords (absorbing sets) whose weight is strictly smaller than the minimum distance of the code [27].…”
Section: Case Study: Array-based Codesupporting
confidence: 92%
See 2 more Smart Citations
“…We first show in Lemma 1 that (4, 8) absorbing sets indeed exist for this r = 5 array-based code family. This theoretical result is also consistent with previous experimental results of a sum-product decoding algorithm built in software and on a hardware emulator [30] for which it was shown that decoding errors due to (4,8) absorbing sets dominate the low BER region. This error floor region is determined by noncodewords (absorbing sets) whose weight is strictly smaller than the minimum distance of the code [27].…”
Section: Case Study: Array-based Codesupporting
confidence: 92%
“…Previous work [4], [20] studied structural properties of dominant absorbing sets for a representative class of practical regular LDPC codes. Concurrently, absorbing sets were also experimentally verified on a hardware emulator [28], [30] to govern the low BER region performance for several representative LDPC code families.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically it has been observed that, in the case of regular d v = 3 LDPC codes, most harmful (a, b) trapping sets have small values of b. Note that this is necessarily the case for LDPC codes with d v = 4, as explained with the concept of absorbing sets in [18]. In addition, the value of A should be chosen depending on the value of guaranteed error correction capability t that we are trying to achieve, and based on the following conjecture.…”
Section: B Error Setsmentioning
confidence: 99%
“…Let G be the Tanner graph of a binary LDPC code C given by the null space of an m × n matrix H over GF (2). For 1 ≤ κ ≤ n and 0 ≤ τ ≤ m, we have following definitions [3], [8], [11] [11].…”
Section: Trapping Sets: Definitions and Conceptsmentioning
confidence: 99%